Is There Convergence and Causality Between the Drivers of Energy-Related Carbon Dioxide Emissions Among the Portuguese Tourism Industry? - Moutinho, Victor (International Journal of Energy Economics and Policy, 2015)
The various sub-sectors related to tourism have different impacts on the level of emissions but also different factors that contribute to these emissions. The purpose of this paper is to study: (i) whether the various subsectors of tourism in Portugal behaved similarly in the period 1996-2009 inrelation to the intensity of Carbon Dioxide (CO2) emissions and for their determinant ratios. This question is studied through the convergence analysis, dividing tourism subsectors between their direct or indirect impact on tourism industry; and (ii) the prediction of the interaction between the intensity of emissions and its determinant ratios in the future. The lower divergences in tourism activities would facilitate the implementation of measures on how to mitigate CO2 emissions at tourism industry and as a result, commit to Kyoto protocol Keywords: CO2 emissions intensity; Convergence; Decomposition; Generalized variance decomposition; impulse response functions; Tourism; Portugal. JEL Classifications: Q49 ; Q53 ; Q58